Global environment outlook 2000 (Earthscan Pub. LondonGB, 1999)
Provides a comprehensive and authoritative review and annalysis of environmental conditions around the world. Addresses three main areas: the state of the environment; trends and progress in policy development, including multilateral environmetntal agreements; and the future, with a focus on emerging environmental issues and region-specific alternative policies.
Keywords: ENVIRONMENT